ANALISIS KINERJA PEGAWAI DALAM MENINGKATKAN KUALITAS PELAYANAN DI KANTOR KECAMATAN KLANGENAN KABUPATEN CIREBON - Adityo Gumilar; I Machmud; RM Haryo Bharoto (Universitas Swadaya Gunung Jati, 2018)
ABSTRACTObservational title that writer establishes is “ Analysis Clerk Performance In Increase Public Service quality At Klanegann's district Office Cirebon's Regency.” Problem that found writer is at t clerk performance / service officer that was maximal, because of its reducing disciplined by job of clerk Still available clerk which haven't understood TUPOKSI and its SOP so even performance not mencapa target.Identify problem in observational which is: 1) How clerk performance at Klangenan's district Office Cirebon's Regency, 2) How Ministering qualities at KlangenanKabuapten Cirebon's district Office 3) factor what do constrain clerk performance to ministering quality step-ups at Klangenan's district Office Cirebon's Regency.Observational method that utilized by writer is methodic qualitative descriptive approaching with take research location at Klangenan's district Cirebon's Regency, be become key informan in observational it is Ministering Common, meanwhile data collecting tech is with library study, interview and direct observation.Research's result prove clerk performance at Klangenan's district stills haven't maximal this proofed of observation and interview that done by writer which is still available clerk which haven't menguasi IT, still marks sense clerk that haven't understood TUPOKSI and SOP, so service's quality by peoples was utterly materializes, this was proven writerfrom tab's result, which is: facilities is service's supporter stills less, clerk was posed friendly to ministering petitioner.